A method for preparing a coating layer by coaxial alternating magnetic field assisted laser cladding
Patent Information
- Application Number
- CN202611436842.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-16
- Publication Date
- 2026-10-30
AI Technical Summary
[0005]针对现有技术的不足,本发明提供了一种同轴交变磁场辅助激光熔覆制备涂层的方法,解决了纯激光熔覆过程中极易产生热应力冷裂纹,和单纯采用感应加热导致熔池内元素严重热稀释偏析、枝晶粗化和碳化物发生严重脱碳分解的问题
1、本发明通过开启同轴交变磁场发生装置在金属熔池位置产生交变磁场,交变磁场在液态金属内部诱导产生交变洛伦兹力,驱动金属熔池产生旋转式强制涡旋对流,强制涡旋对流的流速大于金属熔池内部自然对流的流速,打破了铁元素、铬元素和镍元素沿温度梯度的定向扩散状态,促使铁元素、铬元素和镍元素在三维空间内充分混合,减小了局部热点区域的溶质聚集现象,实现了熔覆涂层内部元素的均质化分布,消除了基体铁元素进入金属熔池形成的热稀释偏析缺陷。
Smart Images

Figure CN123005380A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of laser cladding technology, specifically to a method for preparing coatings by laser cladding assisted by a coaxial alternating magnetic field. Background Technology
[0002] In the process of laser cladding for ceramic-metal coatings, the laser beam exhibits rapid heating and cooling characteristics. The large temperature gradient in the laser beam's irradiation area leads to the accumulation of residual tensile stress during the solidification and cooling phase of the molten metal. If this residual tensile stress exceeds the material's fracture strength, it can induce penetrating cold cracks. To eliminate cold cracks, conventional processing methods employ induction heating devices for preheating the substrate.
[0003] Preheating the substrate extends the duration of the molten metal pool. This prolonged high temperature increases the amount of iron dissolving upwards from the substrate into the molten metal pool, causing thermal dilution and segregation defects and reducing the homogenization of elements within the cladding coating. The extended solidification and cooling time also promotes the formation of coarse columnar dendrites within the molten metal pool, undermining the microstructural strengthening effect of the cladding coating.
[0004] The prolonged duration of the molten metal pool exposes chromium carbide particles to a high-temperature liquid environment for an extended period. In this environment, chromium carbide undergoes a phase transformation and decarburization, decomposing to form lower-carbon carbides and free carbon. The hardness of these lower-carbon carbides is lower than that of the original chromium carbide. This decomposition reaction reduces the amount of high-hardness phase retained within the cladding coating, thus weakening its wear resistance. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this invention provides a method for preparing coatings using coaxial alternating magnetic field-assisted laser cladding. This method solves the problems of easily generating thermal stress cold cracks during pure laser cladding and the severe thermal dilution and segregation of elements, dendrite coarsening, and severe decarburization and decomposition of carbides in the molten pool caused by simply using induction heating.
[0006] To achieve the above objectives, the present invention provides the following technical solution: This invention provides a method for preparing coatings using coaxial alternating magnetic field-assisted laser cladding, comprising the following steps: Cr3C2 powder and NiCr powder are fed into a powder mixer to be mixed to obtain a mixed material. The mixed material is then screened through a mesh screen to obtain a mixture. The surface of the 45# steel substrate to be clad was polished with sandpaper and cleaned with anhydrous ethanol to obtain a 45# steel substrate with the oxide layer and oil removed. The induction heating equipment is used to heat and keep the 45# steel substrate, after the oxide layer and oil stains have been removed, at the desired temperature. Turn on the coaxial alternating magnetic field generator and laser processing equipment. The coaxial alternating magnetic field generator generates an alternating magnetic field at the laser cladding position with the magnetic field axis coaxially aligned with the laser beam axis. A protective gas is introduced, and a carrier gas is used to coaxially transport the mixed material into the alternating magnetic field. The laser processing equipment is used to perform laser melting on the surface of the 45# steel substrate after the oxide layer and oil have been removed to form a metal pool. The 45# steel substrate containing the molten metal pool is placed in an air environment for cooling to generate a coating prepared by laser cladding with a coaxial alternating magnetic field.
[0007] By employing the above technical solution, the use of induction heating equipment to heat and maintain the 45# steel substrate reduces the solid-liquid interface temperature gradient, lowers residual thermal stress, and prevents cold cracking. Simultaneously, the use of a coaxial alternating magnetic field generator to produce an alternating magnetic field at the laser cladding location, acting on the high-temperature conductive liquid metal pool to generate alternating Lorentz forces, drives forced vortex convection in the molten metal pool, achieves fine-grain strengthening of the microstructure, and regulates the homogenization distribution of elements and phase transformation evolution, suppressing high-temperature decarburization and decomposition of carbides. Therefore, a cladding coating with no macroscopic cracks, uniform element distribution, and high hardness carbide retention rate is obtained.
[0008] Conventional heating causes the iron in the matrix to dissolve thermally and enter the molten pool, resulting in thermal dilution and segregation. An alternating magnetic field generates spatially symmetrical alternating Lorentz forces within the molten metal pool, creating a rotating, forced vortex convection. The flow velocity of this forced vortex convection is greater than that of natural convection, disrupting the directional diffusion of elements along the temperature gradient. Iron, chromium, and nickel elements are thoroughly mixed in three-dimensional space, reducing solute accumulation in local hot spots and achieving a homogeneous distribution of elements within the coating.
[0009] Chromium carbide exhibits a spontaneous decarburization tendency in a high-temperature liquid environment, undergoing a decarburization reaction to generate low-carbon carbides and free carbon. On one hand, forced vortex convection enhances the mass transfer rate within the molten metal pool. Liquid metal in the locally hot, overheated areas of the molten metal pool rapidly flows away, replacing the liquid metal in the lower-temperature edge areas. This liquid metal replacement process induced by forced vortex convection shortens the residence time of chromium carbide particles in the high-temperature decarburization zone. On the other hand, homogenized elemental distribution reduces the chemical potential gradient of carbon in the molten pool, mitigating the driving force of the decarburization reaction and inhibiting its decarburization.
[0010] The shear force generated by the forced vortex convection erodes and breaks up the nascent columnar dendrites growing at the solid-liquid interface. The free dendrite fragments enter the molten pool and act as new heterogeneous nucleation sites. At the same time, the flow of liquid metal homogenizes the temperature field of the entire molten pool, reduces the temperature gradient at the solidification interface, and promotes the transformation of the coating grains from coarse columnar dendrites to fine equiaxed grains.
[0011] Preferably, the prepared mixture consists of 20-30 parts by mass of the Cr3C2 powder and 70-80 parts by mass of the NiCr powder.
[0012] By adopting the above technical solution, maintaining a limited amount of Cr3C2 powder by weight ensures that the coating has a sufficient source of hard phase particles, providing basic wear resistance. At the same time, the limited amount of NiCr powder melts to form a matrix phase with good toughness and corrosion resistance. During solidification, it coats the incompletely melted Cr3C2 particles, buffering stress and preventing the coating from becoming brittle.
[0013] Preferably, the specific conditions for mixing and screening are as follows: the speed of the mixer is controlled at 200-400 r / min for 1-3 hours, and the mixed material is screened through a mesh screen to obtain a mixture with a particle size in the range of 40-180 μm.
[0014] By adopting the above technical solution, the powder particle size is controlled within the specified range, ensuring the flowability of the powder in the powder feeding pipe and avoiding agglomeration and blockage caused by excessively fine powder. When the powder within the specified particle size range passes through the laser beam, it can absorb an appropriate amount of energy and reach a micro-melted state before falling into the molten pool, improving the powder deposition rate and avoiding incomplete melting defects caused by excessively large powder and excessive burn-off caused by excessively small powder.
[0015] Preferably, the specific conditions for heating and holding the 45# steel substrate after removing the oxide layer and oil are as follows: operate the induction heating equipment to raise the temperature of the 45# steel substrate after removing the oxide layer and oil to 450-550℃ and hold it for 10-30 minutes.
[0016] By employing the above technical solution, preheating the substrate to the specified temperature range and holding it at that temperature reduces the initial temperature difference between the liquid metal and the solid substrate, thus lowering the cooling rate during solidification. The slower cooling rate provides a time window for residual thermal stress release, eliminating stress-induced cracking at its thermodynamic source. Limiting the maximum heating temperature within a set value prevents excessive thermal activation of the iron elements in the substrate, and, in conjunction with the alternating magnetic field, suppresses excessive thermal dilution of the substrate.
[0017] Preferably, the specific implementation of generating the alternating magnetic field is as follows: the induction coil of the coaxial alternating magnetic field generator is coaxially fixedly connected to the laser head of the laser processing equipment, the output of the coaxial alternating magnetic field generator is adjusted to an alternating current of 1100-1300A, and the output of the coaxial alternating magnetic field generator is adjusted to an oscillation frequency of 40-60kHz.
[0018] By adopting the above technical solution, the coaxial fixed arrangement ensures that the center of the alternating magnetic field coincides with the center of the laser beam, generating a spatially symmetrical electromagnetic force distribution within the molten pool. This prevents unidirectional accumulation caused by asymmetrical force fields and ensures the smoothness of the coating surface. Controlling the alternating current and oscillation frequency within the specified numerical range ensures the penetration of electromagnetic energy into the liquid metal, inducing an induced current capable of overcoming natural convection resistance, forming a steady-state forced vortex flow field, and guaranteeing the mass transfer homogenization effect.
[0019] Preferably, the alternating current enters the induction coil, which has a diameter of 55-60 mm and 5-7 turns.
[0020] By adopting the above technical solution and using induction coils with a set diameter and number of turns, a spatially coupled magnetic field environment is formed that matches the interaction area between the substrate and the light spot, thereby improving the spatial conversion rate of magnetic field energy.
[0021] Preferably, the strength of the generated alternating magnetic field is 0.15 to 0.25 T.
[0022] By adopting the above technical solution, the set alternating magnetic field strength determines the magnitude of the electromagnetic stirring force. The magnetic field strength within a limited range can generate forced convection that meets the shear force required to break columnar dendrites, while avoiding the problems of molten pool churning and liquid metal splashing caused by excessive magnetic field strength.
[0023] Preferably, the specific parameters for laser melting are: adjusting the laser power of the laser processing equipment to 2500-2800W and adjusting the laser scanning speed of the laser processing equipment to 10-12mm / s.
[0024] By employing the above technical solution, the laser power within a defined range provides the input heat source that enables the powder and surface metal to melt synchronously. Combined with the scanning speed within the defined range, the heat input per unit area is controlled, ensuring that the width and depth of the molten pool are proportionate, guaranteeing the quality of the metallurgical bond, and avoiding grain coarsening caused by excessive heat input.
[0025] Preferably, the specific conditions for conveying the mixture are as follows: argon gas with a flow rate of 4-6 L / min is used as the carrier gas, and the mixture is coaxially conveyed into the alternating magnetic field at a rate of 10-12 g / min; wherein argon gas with a flow rate of 10-15 L / min is introduced as a protective gas.
[0026] By adopting the above technical solution, and setting a preset powder feeding rate that matches the laser parameters, it is ensured that the powder entering the laser spot area per unit time can completely absorb energy and melt. A stable powder feeding rate maintains the uniformity of the coating thickness and avoids the problem of substrate ablation caused by excessive powder blocking the laser beam or insufficient powder.
[0027] Preferably, the specific method for cooling is to place the 45# steel substrate containing the molten metal pool in the air environment at 20-30°C for cooling.
[0028] By adopting the above technical solution, natural cooling is performed in ambient air, simplifying the operation and reducing process complexity and equipment costs. The moderate ambient temperature avoids secondary thermal stress caused by rapid cooling, ensuring the final structural integrity of the molded part.
[0029] This invention provides a method for preparing coatings using coaxial alternating magnetic field-assisted laser cladding. It offers the following advantages: 1. This invention generates an alternating magnetic field at the location of the molten metal pool by activating a coaxial alternating magnetic field generator. The alternating magnetic field induces an alternating Lorentz force inside the liquid metal, driving the molten metal pool to generate a rotating forced vortex convection. The flow velocity of the forced vortex convection is greater than the flow velocity of the natural convection inside the molten metal pool, breaking the directional diffusion state of iron, chromium and nickel elements along the temperature gradient, promoting the full mixing of iron, chromium and nickel elements in three-dimensional space, reducing the solute aggregation phenomenon in local hot spots, realizing the homogeneous distribution of elements inside the cladding coating, and eliminating the thermal dilution segregation defects caused by the entry of iron elements from the matrix into the molten metal pool.
[0030] 2. This invention enhances the mass transfer rate within the molten metal pool by driving forced vortex convection through an alternating magnetic field. This causes the liquid metal in the high-temperature hotspot region of the molten metal pool to flow away rapidly and replace the liquid metal in the low-temperature edge region. This shortens the residence time of chromium carbide particles in the high-temperature decarburization region. Furthermore, the homogenized distribution of elements reduces the chemical potential gradient of carbon in the molten metal pool, slows down the driving force of the decarburization reaction, inhibits the decomposition reaction of chromium carbide into low-carbon carbides in the high-temperature liquid environment, and increases the retention of high-hardness carbide phases within the cladding coating.
[0031] 3. This invention generates shear force inside the molten metal pool through forced vortex convection. The shear force scours and breaks up the nascent columnar dendrites growing at the solid-liquid interface. The broken dendrite fragments enter the molten metal pool and act as non-uniform nucleation nuclei. At the same time, the circulating flow of liquid metal homogenizes the temperature field distribution inside the molten metal pool, reduces the temperature gradient at the solidification interface, and promotes the transformation of the grain morphology of the cladding coating from coarse columnar dendrites to fine equiaxed crystals, thus completing the fine-grain strengthening process of the microstructure. Attached Figure Description
[0032] Figure 1 The electromagnetic stirring flow velocity distribution curves along the depth direction of the molten metal pool under different process conditions of the present invention are shown. Figure 2 This is a graph showing the evolution of the center temperature of the molten metal pool over time under different process conditions according to the present invention; Figure 3 The graph shows the Fe element distribution curves along the depth direction of the coating cross section under different process conditions of the present invention. Figure 4 These are X-ray diffraction patterns of the coating surface under different process conditions according to the present invention; Figure 5 This is a distribution diagram showing the change in coating wear quality loss with wear test time under different process conditions of the present invention. Detailed Implementation
[0033] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the test examples of the present invention. Example 1
[0034] This embodiment provides a method for preparing a coating using coaxial alternating magnetic field-assisted laser cladding, including the following steps: S1. Weigh 25 parts by weight of Cr3C2 powder and 75 parts by weight of NiCr powder, and feed the 25 parts by weight of Cr3C2 powder and 75 parts by weight of NiCr powder into a powder mixer. Mix at a speed of 300 r / min for 2 hours. Screen the mixed material through a mesh screen to obtain a mixture with a particle size in the range of 80 μm to 120 μm. S2. Provide a 45# steel substrate to be clad, use sandpaper to polish the processing surface of the 45# steel substrate to be clad, and use anhydrous ethanol to clean the polished processing surface of the 45# steel substrate to be clad, thus obtaining a 45# steel substrate with the oxide layer and oil removed. S3. Start the induction heating equipment and operate the induction heating equipment to heat the 45# steel substrate after removing the oxide layer and oil stains. Raise the temperature of the 45# steel substrate after removing the oxide layer and oil stains to 500℃ and keep it at that temperature for 20 minutes to achieve a constant preheating state for the 45# steel substrate. S4. With the 45# steel substrate preheated to a constant temperature, turn on the coaxial alternating magnetic field generator and the laser processing equipment. Coaxially connect the induction coil of the coaxial alternating magnetic field generator to the laser head of the laser processing equipment. Adjust the output of the coaxial alternating magnetic field generator to 1200A alternating current and adjust the output oscillation frequency of the coaxial alternating magnetic field generator to 50kHz. The alternating current enters the induction coil with a diameter of 58mm and 6 turns, generating an alternating magnetic field at the laser cladding position whose magnetic field axis is coaxially aligned with the laser beam axis. The intensity of the alternating magnetic field is 0.20T. Simultaneously adjust the laser head of the laser processing equipment... The optical power is 2694W, the laser scanning speed of the laser processing equipment is adjusted to 11mm / s, argon gas with a flow rate of 5L / min is used as the carrier gas, and the mixture with a particle size in the range of 80μm to 120μm is coaxially transported into the alternating magnetic field at a rate of 11g / min. At the same time, argon gas with a flow rate of 12L / min is introduced as a protective gas, and laser melting is carried out. The molten liquid metal is subjected to Lorentz force in the alternating magnetic field, and a metal pool with forced convection vortex is constructed on the surface of the 45# steel substrate after the oxide layer and oil are removed, breaking the directional diffusion of elements along the temperature gradient. S5. Turn off the induction heating equipment, the coaxial alternating magnetic field generator and the laser processing equipment, and place the 45# steel substrate containing the forced convection vortex molten metal pool in an air environment at 25°C for cooling, thereby generating a coating prepared by coaxial alternating magnetic field-assisted laser cladding. Example 2
[0035] This embodiment provides a method for preparing a coating using coaxial alternating magnetic field-assisted laser cladding, including the following steps: S1. Weigh 30 parts by weight of Cr3C2 powder and 70 parts by weight of NiCr powder, and feed them into a powder mixer. Mix at 400 r / min for 3 hours. Screen the mixed material through a screen to obtain a mixture with a particle size in the range of 120 μm to 180 μm. S2. Provide a 45# steel substrate to be clad, use sandpaper to polish the processing surface of the 45# steel substrate to be clad, and use anhydrous ethanol to clean the polished processing surface of the 45# steel substrate to be clad, thus obtaining a 45# steel substrate with the oxide layer and oil removed. S3. Start the induction heating equipment and operate the induction heating equipment to heat the 45# steel substrate after removing the oxide layer and oil stains. Raise the temperature of the 45# steel substrate after removing the oxide layer and oil stains to 550℃ and keep it at that temperature for 30 minutes to achieve a constant preheating state for the 45# steel substrate. S4. With the 45# steel substrate preheated to a constant temperature, turn on the coaxial alternating magnetic field generator and the laser processing equipment. Coaxially connect the induction coil of the coaxial alternating magnetic field generator to the laser head of the laser processing equipment. Adjust the output of the coaxial alternating magnetic field generator to 1300A alternating current and the output oscillation frequency to 60kHz. The alternating current enters the induction coil with a diameter of 60mm and 7 turns, generating an alternating magnetic field at the laser cladding position whose magnetic field axis is coaxially aligned with the laser beam axis. The intensity of the alternating magnetic field is 0.25T. Simultaneously adjust the laser head of the laser processing equipment... The optical power is 2800W, the laser scanning speed of the laser processing equipment is adjusted to 12mm / s, argon gas with a flow rate of 6L / min is used as the carrier gas, and the mixture with a particle size in the range of 120μm to 180μm is coaxially transported into the alternating magnetic field at a rate of 12g / min. At the same time, argon gas with a flow rate of 15L / min is introduced as a protective gas, and laser melting is carried out. The molten liquid metal is subjected to Lorentz force in the alternating magnetic field, and a metal pool with forced convection vortex is constructed on the surface of the 45# steel substrate after the oxide layer and oil are removed, breaking the directional diffusion of elements along the temperature gradient. S5. Turn off the induction heating equipment, the coaxial alternating magnetic field generator and the laser processing equipment, and place the 45# steel substrate containing the forced convection vortex molten metal pool in an air environment at 30°C for cooling, thereby generating a coating prepared by coaxial alternating magnetic field-assisted laser cladding. Example 3
[0036] This embodiment provides a method for preparing a coating using coaxial alternating magnetic field-assisted laser cladding, including the following steps: S1. Weigh 20 parts by weight of Cr3C2 powder and 80 parts by weight of NiCr powder, and feed them into a powder mixer. Mix them at a speed of 200 r / min for 1 hour. Then, screen the mixed material through a screen to obtain a mixture with a particle size in the range of 40 μm to 70 μm. S2. Provide a 45# steel substrate to be clad, use sandpaper to polish the processing surface of the 45# steel substrate to be clad, and use anhydrous ethanol to clean the polished processing surface of the 45# steel substrate to be clad, thus obtaining a 45# steel substrate with the oxide layer and oil removed. S3. Start the induction heating equipment and operate the induction heating equipment to heat the 45# steel substrate after removing the oxide layer and oil stains. Raise the temperature of the 45# steel substrate after removing the oxide layer and oil stains to 450℃ and keep it at that temperature for 10 minutes to achieve a constant preheating state for the 45# steel substrate. S4. With the 45# steel substrate preheated to a constant temperature, turn on the coaxial alternating magnetic field generator and the laser processing equipment. Coaxially connect the induction coil of the coaxial alternating magnetic field generator to the laser head of the laser processing equipment. Adjust the output of the coaxial alternating magnetic field generator to 1100A alternating current and adjust the output oscillation frequency to 40kHz. The alternating current enters the induction coil with a diameter of 55mm and 5 turns, generating an alternating magnetic field at the laser cladding position whose magnetic field axis is coaxially aligned with the laser beam axis. The strength of the alternating magnetic field is 0.15T. Simultaneously adjust the laser processing equipment... The laser power is 2500W, the laser scanning speed of the laser processing equipment is adjusted to 10mm / s, argon gas with a flow rate of 4L / min is used as the carrier gas, and the mixture with a particle size in the range of 40μm to 70μm is coaxially transported into the alternating magnetic field at a rate of 10g / min. At the same time, argon gas with a flow rate of 10L / min is introduced as a protective gas, and laser melting is carried out. The molten liquid metal is subjected to Lorentz force in the alternating magnetic field, and a metal pool with forced convection vortex is constructed on the surface of the 45# steel substrate after the oxide layer and oil are removed, breaking the directional diffusion of elements along the temperature gradient. S5. Turn off the induction heating equipment, the coaxial alternating magnetic field generator and the laser processing equipment, and place the 45# steel substrate containing the forced convection vortex molten metal pool in an air environment at 20°C for cooling, thereby generating a coating prepared by coaxial alternating magnetic field-assisted laser cladding.
[0037] Comparative Example 1: Compared with Example 1, the difference is that the coaxial alternating magnetic field generator was not turned on, and no alternating magnetic field was generated at the laser cladding position; all other aspects are the same.
[0038] Comparative Example 2: Compared with Example 1, the difference is that in step S4, the current of the input induction coil is replaced with a constant DC current of 1200A, no oscillation frequency is output, and a steady static magnetic field with an intensity of 0.20T is generated at the laser cladding position. All other aspects are the same.
[0039] Comparative Example 3: Compared with Example 1, the difference is that in step S4, the induction coil and the laser head of the laser processing equipment are arranged vertically to the side, and the magnetic field axis that generates the magnetic field is perpendicular to the laser beam axis. All other aspects are the same.
[0040] Test Example 1: The test equipment was operated, and an oscilloscope and a current probe were connected to the output of the high-frequency induction power supply to acquire the alternating current waveform and frequency parameters of the induction coil entering the coaxial alternating magnetic field generator. A Hall effect gaussmeter probe was fixed inside the induction coil of the coaxial alternating magnetic field generator, and the probe position was controlled at the laser cladding position to record the alternating magnetic field strength. With the laser processing equipment turned on, the conductivity of the molten liquid metal was measured using the high-temperature four-probe method, and the density of the solid metal at room temperature was measured using the water displacement method. The density of the liquid metal was then calculated based on the coefficient of thermal expansion of the liquid metal.
[0041] The process operating parameters of Examples 1, 2, and 3, and Comparative Examples 1, 2, and 3 were retrieved. Based on Maxwell's equations and Faraday's law of electromagnetic induction, the measured values of alternating magnetic field strength and liquid metal conductivity were imported to calculate the Lorentz force density under different process conditions. The viscosity coefficient of the liquid metal at a specified temperature was obtained, and a fluid dynamics model was established based on the Navier-Stokes equations. The peak flow velocity of the electromagnetically stirred forced convection vortex was calculated using the Lorentz force density values. The natural thermal convection flow velocity under conditions where no alternating magnetic field was applied to the liquid metal was recorded as a baseline reference. The numerical values were summarized to generate a test result report.
[0042] Table 1. Lorentz force parameters and flow rate test results under different process conditions Example 1 0.198 49.8 51324.6 0.243 Example 2 0.252 60.1 64817.2 0.338 Example 3 0.153 40.2 38102.5 0.165 Comparative Example 1 0.000 0.0 0.0 0.041 Comparative Example 2 0.201 0.0 0.0 0.038 Comparative Example 3 0.197 49.7 29451.8 0.126 Figure 1 This is a graph showing the distribution of electromagnetic stirring flow rate along the depth of the molten liquid metal pool under different process conditions of the present invention. The horizontal axis of the graph represents the depth of the molten liquid metal pool (mm), and the vertical axis represents the electromagnetic stirring flow rate (m / s). The curves in the graph represent the changes in electromagnetic stirring flow rate at different depths of the molten liquid metal pool for Examples 1, 2, 3, Comparative Examples 1, 2, and 3, respectively.
[0043] in conclusion: According to Table 1 and Figure 1 The data shows that after the coaxial alternating magnetic field generator was turned on in Examples 1, 2, and 3, the alternating current output by the coaxial alternating magnetic field generator produced an alternating magnetic field in the induction coil. The oscillation frequency of the alternating magnetic field was in the range of 40kHz to 60kHz, and the intensity of the alternating magnetic field was in the range of 0.15T to 0.25T. The liquid metal inside the alternating magnetic field generated induced eddy currents, and the interaction between the induced eddy currents and the alternating magnetic field generated a Lorentz force density. The Lorentz force density drove the liquid metal to flow, generating a molten metal pool with forced convection vortices inside. The peak electromagnetic stirring flow rate in Examples 1, 2, and 3 was higher than the natural thermal convection flow rate in Comparative Example 1.
[0044] Comparing the data states of Example 1 and Comparative Example 1, Comparative Example 1 did not activate the coaxial alternating magnetic field generator, and the Lorentz force volume density was zero. In Comparative Example 1, the liquid metal relied solely on surface tension generated by the internal temperature gradient for thermal motion, resulting in a natural thermal convection velocity of 0.041 m / s. The Lorentz force volume density of Example 1 reached 51324.6 N / m³. 3 The peak flow rate of the electromagnetic stirring reached 0.243 m / s. The forced convection vortex changed the mass transfer state of 25 parts by mass of Cr3C2 powder and 75 parts by mass of NiCr powder after melting, breaking the directional diffusion of elements along the temperature gradient.
[0045] Comparing the data states of Example 1 and Comparative Example 2, Comparative Example 2 input a constant DC current of 1200A and generated a steady static magnetic field with an intensity of 0.20T. When the steady static magnetic field passed through the liquid metal, it failed to induce eddy current waves and did not generate the Lorentz force density that drives the flow. The steady static magnetic field produced a magnetic damping effect on the thermal convection of the liquid metal, reducing the peak flow velocity of the electromagnetic stirring to 0.038 m / s. The steady static magnetic field alone slowed down the flow velocity inside the liquid metal.
[0046] Comparing the data states of Example 1 and Comparative Example 3, in Comparative Example 3, the induction coil is arranged perpendicularly to the laser head of the laser processing equipment, resulting in a Lorentz force density reduced to 29451.8 N / m³. 3 The peak flow velocity of the electromagnetic stirring decreased to 0.126 m / s. The perpendicular intersection of the magnetic field axis and the laser beam axis caused a mismatch between the magnetic field distribution in space and the fluid field boundary, which weakened the transmission depth of the force field in the depth direction of the molten metal pool and reduced the stirring effect.
[0047] Test Example 2: Fix the dual-color infrared thermometer to the frame of the laser processing equipment, adjust the measuring optical path of the dual-color infrared thermometer, and align the measuring focus with the laser cladding position on the surface of the 45# steel substrate after removing the oxide layer and oil.
[0048] With the 45# steel substrate preheated to a constant temperature, the laser processing equipment and coaxial alternating magnetic field generator were turned on to carry out the laser melting process. A dual-color infrared thermometer was used to continuously collect the temperature value at the center of the molten metal pool, recording the temperature evolution over time, extracting the temperature change history, and generating a curve showing the temperature evolution of the molten metal pool center over time.
[0049] Based on the thermodynamic initiation conditions of the decarburization reaction, 1400℃ was set as the critical decarburization temperature for calculation. The evolution curve of the center temperature of the molten metal pool over time was read, and the integral interval where the center temperature of the molten metal pool is higher than the critical decarburization temperature was extracted. The residence time of the molten metal pool center temperature above the critical decarburization temperature was then calculated.
[0050] Temperature measurement records from Examples 1, 2, 3, Comparative Examples 1, 2, and 3 were retrieved, and data parameters of peak temperature and dwell time were summarized and organized.
[0051] Table 2. Test results of residence time in the high-temperature zone of molten metal pool under different process conditions Example 1 2135.4 65.2 Example 2 2187.9 58.7 Example 3 2056.2 73.4 Comparative Example 1 2204.3 182.5 Comparative Example 2 2215.8 195.1 Comparative Example 3 2178.6 141.8 Figure 2 This is a graph showing the evolution of the center temperature of the molten metal pool over time under different process conditions of the present invention. The horizontal axis represents the test time (ms), and the vertical axis represents the center temperature of the molten metal pool (°C). The curves in the graph represent the changes in the center temperature of the molten metal pool under different test times for Examples 1, 2, 3, Comparative Examples 1, 2, and 3, respectively.
[0052] in conclusion: According to Table 2 and Figure 2 The data shows that after the coaxial alternating magnetic field generator was activated in Examples 1, 2, and 3, it constructed a molten metal pool with forced convection vortices inside the 45# steel substrate surface after the oxide layer and oil stains were removed. The forced convection vortex accelerated the heat transfer rate inside the molten metal pool, changing the thermal cycle of the Cr3C2 powder and NiCr powder mixture after melting. In Examples 1, 2, and 3, the residence time above the decarburization critical temperature of the center temperature of the molten metal pool was between 58.7 ms and 73.4 ms.
[0053] In Comparative Example 1, the coaxial alternating magnetic field generator was not activated, and heat exchange within the molten metal pool relied on natural thermal convection. In Comparative Example 1, the residence time above the decarburization critical temperature in the center of the molten metal pool reached 182.5 ms. This prolonged high-temperature exposure provided the thermodynamic time conditions for the decarburization decomposition reaction of the Cr3C2 powder. In Example 1, compared to Comparative Example 1, the molten metal pool with internal forced convection vortices shortened the residence time above the decarburization critical temperature to 65.2 ms. The forced convection vortex caused the molten metal in the local high-temperature zone to flow away rapidly, and the molten metal in the surrounding low-temperature zone replaced the flowing high-temperature molten metal, limiting the time range for the carbide decomposition reaction.
[0054] Comparative Example 2 generates a steady static magnetic field at the laser cladding location. This steady static magnetic field exerts a magnetic damping effect on the liquid metal, slowing down the heat exchange rate within the molten metal pool. In Comparative Example 2, the residence time of the liquid metal pool center temperature above the decarburization critical temperature increases to 195.1 ms, exacerbating the time accumulation of the decarburization decomposition reaction.
[0055] In Comparative Example 3, the induction coil is arranged perpendicularly to the laser head of the laser processing equipment. The non-coaxial alternating magnetic field generates asymmetrical fluid motion inside the molten metal pool, resulting in a lower heat exchange efficiency than in Example 1. In Comparative Example 3, the residence time of the liquid metal pool center temperature evolution curve above the decarburization critical temperature is 141.8 ms. The coaxial fixed arrangement of the coaxial alternating magnetic field generator constructs a spatially symmetrical state of forced convection vortex, accelerating the overall homogenization and heat transfer rate.
[0056] Test Example 3: A 45# steel substrate sample containing the coating was extracted, and a cross-section of the coating was cut using an electrical discharge wire cutter perpendicular to the laser scanning direction. The coated cross-section was then sanded with sandpaper and cleaned with anhydrous ethanol. The cleaned sample was then placed in a scanning electron microscope testing chamber equipped with an energy dispersive spectroscopy (EDS) instrument.
[0057] The energy dispersive spectrometer (EDS) was used to set a test path along the depth direction of the coating cross-section, and data was collected from the coating surface towards the 45# steel substrate at the same spacing. The spacing between adjacent test points was set to 10 μm. Without outputting surface scan images, the absolute atomic percentage values of Fe and Cr at each test point were directly extracted.
[0058] Data from measurement points along the depth direction of the coating cross-section were retrieved for Examples 1, 2, 3, Comparative Examples 1, 2, and 3. The maximum and minimum values of Fe content in each group of samples were extracted, and the range (maximum minus minimum) was calculated to reflect the fluctuation range of Fe content. The standard deviation of Cr content was calculated based on the absolute atomic percentage of Cr at each measurement point. A test report was generated by summarizing the collected numerical parameters.
[0059] Table 3. Test results of range and standard deviation of elemental content in coating cross sections under different process conditions Example 1 20.49 14.38 6.11 1.52 Example 2 19.85 14.12 5.73 1.45 Example 3 21.06 14.28 6.78 1.63 Comparative Example 1 35.28 12.83 22.45 4.18 Comparative Example 2 33.62 13.05 20.57 3.86 Comparative Example 3 28.51 13.79 14.72 2.84 Figure 3 This is a graph showing the distribution curves of Fe element along the depth direction of the coating cross section under different process conditions of the present invention. The horizontal axis of the graph represents the coating cross section depth (mm), and the vertical axis represents the Fe element content (at.%). The curves in the graph represent the changes in Fe element content at different coating cross section depths for Examples 1, 2, 3, Comparative Examples 1, 2, and 3, respectively.
[0060] in conclusion: According to Table 3 and Figure 3 Data shows that in Examples 1, 2, and 3, the coaxial alternating magnetic field generator was activated, creating a molten metal pool with forced convection vortices on the surface of the 45# steel substrate after the oxide layer and oil contaminants were removed. The forced convection vortex stirred the internal fluid, breaking the directional diffusion of elements along the temperature gradient. The mixture of Cr3C2 powder and NiCr powder achieved three-dimensional mixing in the molten state. The range of Fe element content in Examples 1, 2, and 3 was between 5.73 at.% and 6.78 at.%, and the standard deviation of Cr element content was between 1.45 at.% and 1.63 at.%, with lower data fluctuations than other process states. The coaxial alternating magnetic field altered the thermal diffusion path of Fe element from the 45# steel substrate into the coating, suppressing thermal dilution segregation.
[0061] In Comparative Example 1, the coaxial alternating magnetic field generator was not activated, and mass transfer within the molten metal pool relied on natural thermal convection. In Comparative Example 1, Fe element accumulated near the interface with the 45# steel substrate, reaching a maximum value of 35.28 at.%. The range of Fe element content reached 22.45 at.%, and the standard deviation of Cr element content reached 4.18 at.%. Natural thermal convection could not overcome the preferential element distribution caused by the temperature gradient at the solid-liquid interface, resulting in severe compositional inhomogeneity within the coating cross-section.
[0062] The induction coil in Comparative Example 2 generates a steady static magnetic field. This steady static magnetic field exerts an electromagnetic damping effect on the fluid movement within the molten metal pool, slowing down the flow rate of the liquid metal. The range of Fe content in Comparative Example 2 is 20.57 at.%, and the standard deviation of Cr content is 3.86 at.%. The steady static magnetic field restricts the mixing process of Cr3C2 powder and NiCr powder after melting and cannot eliminate directional diffusion along the temperature gradient.
[0063] In Comparative Example 3, the induction coil is arranged perpendicularly to the laser head of the laser processing equipment, resulting in a non-coaxial alternating magnetic field. The range of Fe content in Comparative Example 3 is 14.72 at.%, and the standard deviation of Cr content is 2.84 at.%. The non-coaxial arrangement causes asymmetric Lorentz forces within the molten metal pool, resulting in a lower degree of fluid mixing compared to a coaxially fixed arrangement of the alternating magnetic field generator. A coaxially fixed arrangement creates a symmetrical mechanical distribution boundary, improving the homogeneity of elemental distribution across the coating cross-section.
[0064] Test Example 4: Extract the 45# steel substrate sample after laser cladding. Cut the coating surface sample using metallographic cutting equipment. Use an automatic polishing machine to grind and polish the coating surface to remove surface oxides. Ultrasonically clean the polished sample surface with anhydrous ethanol and dry it for later use.
[0065] Place the processed sample on the sample stage of the X-ray diffractometer. Set the scanning range of the X-ray diffractometer to between 30° and 60°. Turn on the X-ray diffractometer to perform continuous scanning tests on the sample surface.
[0066] Record the spectral data output by the X-ray diffractometer, extract the intensity values of the diffraction peaks corresponding to the main crystal plane of the skeleton, and simultaneously extract the intensity values of the diffraction peaks corresponding to the characteristic impurities that characterize the decarburization products.
[0067] The intensity data of Examples 1, 2, 3, Comparative Examples 1, 2, and 3 were compiled. The relative percentage values of the diffraction peak intensities of the decarburized products and the diffraction peak intensities of the main framework phase were calculated. The numerical results were compared and summarized to generate a quantitative test table of phase diffraction peak intensities.
[0068] Table 4. Test results of phase diffraction peak intensity of coating surface under different process conditions Example 1 5214 218 4.18 Example 2 5089 196 3.85 Example 3 5302 235 4.43 Comparative Example 1 4125 1546 37.47 Comparative Example 2 3958 1682 42.49 Comparative Example 3 4612 874 18.95 Figure 4 The figures show X-ray diffraction patterns of the coating surface under different process conditions of the present invention. The horizontal axis represents the diffraction angle (2θ / °), and the vertical axis represents the diffraction intensity (au). The curves in the figures represent the diffraction intensity changes of Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, and Comparative Example 3 at different diffraction angles.
[0069] in conclusion: According to Table 4 and Figure 4 The data shows that after the coaxial alternating magnetic field generator was activated in Examples 1, 2, and 3, it generated forced convection vortices inside the molten metal pool. These forced convection vortices accelerated the convective heat transfer rate of the molten metal pool and shortened the extremely high-temperature residence time of the Cr3C2 and NiCr powders after melting. This shortened residence time limited the thermodynamic conditions for the decomposition reaction of the primary carbides, thus inhibiting the decarburization phase transformation of the Cr3C2 powder to generate low-carbon carbides. In Examples 1, 2, and 3, the relative percentage of the diffraction peak intensity of the decarburized products to the main phase was between 3.85% and 4.43%, indicating that a high-hardness phase was retained within the coating.
[0070] In Comparative Example 1, the coaxial alternating magnetic field generator was not activated, and the molten metal pool relied on natural convection for heat dissipation. Natural convection heat transfer was slow, leading to heat accumulation within the molten metal pool. The prolonged high-temperature environment induced decarburization of the primary carbides, generating a large amount of low-carbon carbides. In Comparative Example 1, the relative percentage of the diffraction peak intensity of the decarburized products to the main phase reached 37.47%.
[0071] A steady static magnetic field was applied to Comparative Example 2. This field suppressed the flow of the liquid metal, producing an electromagnetic damping effect. This damping reduced the rate of heat loss and exacerbated heat accumulation in the high-temperature region. This heat accumulation directly led to a deeper decomposition reaction of the carbides, increasing the relative percentage of the diffraction peak intensity of the decarburized products to 42.49% in Comparative Example 2.
[0072] In Comparative Example 3, the induction coils are arranged vertically to the side. The asymmetric fluid mixing caused by the non-coaxial magnetic field results in a lower heat transfer efficiency compared to the coaxial fixed arrangement. In Comparative Example 3, the relative percentage of the diffraction peak intensity of the decarburization products and the main phase is 18.95%. The coaxial arrangement of the coaxial alternating magnetic field generator creates symmetrical mechanical and thermal boundaries, avoiding phase degradation caused by local heat accumulation.
[0073] Test Example 5: Extract the 45# steel substrate sample after laser cladding. Use metallographic cutting equipment to cut mechanical test specimens containing the coating. Use an automatic polishing machine to grind and polish the coating surface of the mechanical test specimens to remove surface oxides. Use anhydrous ethanol to ultrasonically clean the polished coating surface and dry it for later use.
[0074] Place the cleaned mechanical test specimen onto the test platform of the Vickers hardness tester. Set the test load and holding time of the Vickers hardness tester. Operate the Vickers hardness tester to perform a multi-point array indentation test on the coating surface. Record the Vickers hardness value output by the Vickers hardness tester, and calculate the average value of the multi-point test as the average Vickers hardness value of each group of coating surfaces.
[0075] Mount the mechanical test specimen onto the fixture of the friction and wear testing machine. Set the grinding partner of the friction and wear testing machine to GCr15 bearing steel balls, and set a fixed applied load and relative sliding speed. Start the friction and wear testing machine to conduct continuous wear tests. Record the continuous data output by the friction and wear testing machine at different wear test times, and extract the wear mass loss value at the end of the final test. Summarize the average Vickers hardness value and the wear mass loss value to generate a mechanical property test table.
[0076] Table 5. Test results of macroscopic mechanical properties of coatings under different process conditions Example 1 794.6 13.8 Example 2 812.3 12.4 Example 3 785.1 14.5 Comparative Example 1 518.7 38.6 Comparative Example 2 493.2 41.9 Comparative Example 3 647.5 26.3 Figure 5 This is a distribution diagram of the coating wear quality loss under different process conditions of the present invention as a function of wear test time. The horizontal axis of the figure represents the wear test time (min), and the vertical axis represents the wear quality loss (mg). The curves in the figure represent the wear quality loss changes of Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, and Comparative Example 3 under different wear test times.
[0077] in conclusion: According to Table 5 and Figure 5 Data shows that in Examples 1, 2, and 3, the coaxial alternating magnetic field generator was activated. This generator produced forced convection vortices within the molten metal pool. These forced vortices inhibited the decomposition reaction of the primary carbides while promoting the mixing of Cr3C2 and NiCr powders. The high-hardness phase was retained within the coating. The average Vickers hardness values of Examples 1, 2, and 3 ranged from 785.1 HV to 812.3 HV, and the wear mass loss after a 30-minute wear test was controlled within the range of 12.4 mg to 14.5 mg. The retained carbides provided macroscopic hardness support for the coating, and the homogenized microstructure improved the macroscopic wear resistance of the coating.
[0078] Comparative Example 1 did not activate the coaxial alternating magnetic field generator. The thermal accumulation within the molten metal pool led to the decarburization of carbides, generating low-hardness decarburized products. The average Vickers hardness of Comparative Example 1 decreased to 518.7 HV, and the wear mass loss reached 38.6 mg. The loss of the hard phase directly caused a decline in macroscopic mechanical properties.
[0079] A steady static magnetic field was applied to Comparative Example 2. The electromagnetic damping effect generated by the steady static magnetic field exacerbated heat accumulation in the high-temperature region, leading to a deeper decarburization phase transformation. The average Vickers hardness of Comparative Example 2 decreased to 493.2 HV, while the wear mass loss increased to 41.9 mg. Macroscopic wear resistance deteriorated.
[0080] In Comparative Example 3, the induction coil is arranged vertically to the side. The mechanical boundary of the non-coaxial alternating magnetic field structure is asymmetrical, limiting the fluid mixing and homogenization effect. The average Vickers hardness of Comparative Example 3 is 647.5 HV, and the wear mass loss is 26.3 mg. The coaxial fixed arrangement of the coaxial alternating magnetic field generator avoids the problems of local thermal dilution segregation and phase degradation, which is reflected in the final macroscopic performance as an improvement in hardness and wear resistance.
Claims
1. A method for preparing a coating by laser cladding assisted by a coaxial alternating magnetic field, characterized in that, Includes the following steps: Cr3C2 powder and NiCr powder are fed into a powder mixer to be mixed to obtain a mixed material. The mixed material is then screened through a mesh screen to obtain a mixture. The surface of the 45# steel substrate to be clad was polished with sandpaper and cleaned with anhydrous ethanol to obtain a 45# steel substrate with the oxide layer and oil removed. The induction heating equipment is used to heat and keep the 45# steel substrate, after the oxide layer and oil stains have been removed, at the desired temperature. Turn on the coaxial alternating magnetic field generator and the laser processing equipment. The coaxial alternating magnetic field generator generates an alternating magnetic field at the laser cladding position with the magnetic field axis coaxially aligned with the laser beam axis. A protective gas is introduced, and the mixture is coaxially transported into the alternating magnetic field using a carrier gas. The laser processing equipment is then used to perform laser melting on the surface of the 45# steel substrate, after the oxide layer and oil have been removed, to form a molten metal pool. The 45# steel substrate containing the molten metal pool is placed in an air environment for cooling to generate a coating prepared by laser cladding with a coaxial alternating magnetic field.
2. The method for preparing a coating using coaxial alternating magnetic field-assisted laser cladding according to claim 1, characterized in that, The prepared mixture consists of 20-30 parts by mass of the Cr3C2 powder and 70-80 parts by mass of the NiCr powder.
3. The method for preparing a coating using coaxial alternating magnetic field-assisted laser cladding according to claim 1, characterized in that, The specific conditions for mixing and screening are as follows: the speed of the mixer is controlled at 200-400 r / min for 1-3 hours, and the mixed material is screened through a mesh screen to obtain the mixture with a particle size in the range of 40-180 μm.
4. The method for preparing a coating using coaxial alternating magnetic field-assisted laser cladding according to claim 1, characterized in that, The specific conditions for heating and holding the 45# steel substrate after removing the oxide layer and oil are as follows: operate the induction heating equipment to raise the temperature of the 45# steel substrate after removing the oxide layer and oil to 450-550℃ and hold it for 10-30 minutes.
5. The method for preparing a coating using coaxial alternating magnetic field-assisted laser cladding according to claim 1, characterized in that, The specific implementation method for generating the alternating magnetic field is as follows: the induction coil of the coaxial alternating magnetic field generator is coaxially fixedly connected to the laser head of the laser processing equipment, the output of the coaxial alternating magnetic field generator is adjusted to an alternating current of 1100-1300A, and the output of the coaxial alternating magnetic field generator is adjusted to an oscillation frequency of 40-60kHz.
6. The method for preparing a coating using coaxial alternating magnetic field-assisted laser cladding according to claim 5, characterized in that, The alternating current enters the induction coil, which has a diameter of 55-60 mm and 5-7 turns.
7. The method for preparing a coating using coaxial alternating magnetic field-assisted laser cladding according to claim 6, characterized in that, The strength of the generated alternating magnetic field is 0.15 to 0.25 T.
8. The method for preparing a coating by coaxial alternating magnetic field-assisted laser cladding according to claim 1, characterized in that, The specific parameters for laser melting are as follows: adjust the laser power of the laser processing equipment to 2500-2800W, and adjust the laser scanning speed of the laser processing equipment to 10-12mm / s.
9. The method for preparing a coating using coaxial alternating magnetic field-assisted laser cladding according to claim 1, characterized in that, The specific conditions for conveying the mixture are as follows: argon gas with a flow rate of 4-6 L / min is used as the carrier gas, and the mixture is coaxially conveyed into the alternating magnetic field at a rate of 10-12 g / min, wherein argon gas with a flow rate of 10-15 L / min is introduced as the protective gas.
10. The method for preparing a coating using coaxial alternating magnetic field-assisted laser cladding according to claim 1, characterized in that, The specific method for cooling is as follows: the 45# steel substrate containing the molten metal pool is placed in the air environment at 20-30°C for cooling.
